(1+sina+cosa+2sinacosa)/(1+sina+cosa) =[(sina)^2+(cosa)^2+2sinacosa+(sina+cosa)]/(1+sina+cosa) =[(sina+cosa)^2+(sina+cosa)]/(1+sina+cosa) =(sina+cosa)(1+sina+cosa)/(1+sina+cosa) =sina+cosa 还有一种简单的 原式=[sina+cosa+(sina+cosa)^2]/(1+sina+cosa)注:(sina+cosa)^2=1+2sinacosa 令sina+cosa=t 原式=(t+t^2)/(1+t)=t
求证:(1+sinA+cosA+2sinAcos)/(1+sinA+cosA)=sinA+cosA
1个回答
相关问题
-
求证,2(cosA-sinA)/(1+sinA+cosA)=cosA/(1+sinA)-sinA/(1+sinA)
-
求证:(1+sina+cosa+2sinacosa)/(1+sina+cosa)=sina+cosa
-
求证:2(1-sina)(1+cosa)=(1-sina+cosa)²
-
求证:1-cos^2a/sina-cosa - sina+cosa/tan^2a-1=sina+cosa
-
求证tana/2=sina/1+cosa=1-cosa/sina
-
求证:2(1-sina)(1+cosa)=(1-sina+cosa)^2
-
求证:2(1-sina)(1+cosa)=(1-sina+cosa)^2
-
证明:(1+sina-cosa)/(1-sina-cosa)+(1-sina-cosa)/(1+sina-cosa)=-
-
求证:(1+sinA-cosA)/(1+sinA+cosA)=tan(A/2)
-
1.化简(1+cosa-sina)/(1-cosa-sina)+(1-cosa-sina)/(1+cosa-sina)